Patch Adams - Adams, Patch, 1945-; Hoffman, Philip Seymour, 1967-; Mylander, Maureen; Oedekerk, Steve; Potter, Monica; Shadyac, Tom.; Shaiman, Marc.; Williams, Robin, 1952 Julio 21-; Universal Pictures (Firma); Universal Studios Home Video (Firma) (Universal City, CA : Universal Home Video, 2001)
Patch Adams es un doctor como ningún otro que cree que la risa es la mejor medicina, incluso, hasta cuando su carrera esta en riesgo.
Based on the book: Gesundheit : good health is a laughing matter / Hunter Doherty Adams with Maureen Mylander.
Originalmente publicada como película en 1998.
Director of photography, Phedon Papamichael; production design, Linda DeScenna; editor, Don Zimmerman; music, Marc Shaiman.
Robin Williams, Monica Potter, Philip Seymour-Hoffman, Daniel London, Peter Coyote.
MPAA rating: PG-13.
DVD.
Keywords: Adams, Patch, -- 1945-; Gesundheit Institute; Médico y paciente; Películas cinematográficas